2010
DOI: 10.1021/ja1053829
|View full text |Cite
|
Sign up to set email alerts
|

Formal [2 + 2 + 2] Cycloaddition Strategy Based on an Intramolecular Propargylic Ene Reaction/Diels−Alder Cycloaddition Cascade

Abstract: A formal, metal-free, [2 + 2 + 2] cycloaddition strategy is described based on a cascade of two pericyclic processes. The first step involves an intramolecular propargylic ene reaction of a 1,6-diyne to generate a vinylallene, which then reacts in an inter-or intramolecular Diels-Alder reaction with an alkenyl or alkynyl dienophile. Reactions involving unsymmetrical alkenyl and alkynyl dienophiles proceed with good to excellent regioselectivity, and the diastereoselectivity in the Diels-Alder step is also high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 20 publications
2
37
0
1
Order By: Relevance
“…1 Pyridines are one of the most prevalent aromatic heterocycles found in bioactive molecules and functional materials. 2 Cascade pericyclic processes 3 such as merged cycloaddition/ cycloreversion strategies, 4 particularly those employing 1,2,3- and 1,2,4-triazines, 5 are a valuable synthetic complement to traditional and more contemporary 6 condensation methods. 7 In comparison, merged cycloaddition/cycloreversion approaches for the direct synthesis of 2-pyridones are not common; 8 however, Hoornaert and co-workers validated the possibility of this approach using cycloaddition of chlorinated pyrazinone intermediates.…”
mentioning
confidence: 99%
“…1 Pyridines are one of the most prevalent aromatic heterocycles found in bioactive molecules and functional materials. 2 Cascade pericyclic processes 3 such as merged cycloaddition/ cycloreversion strategies, 4 particularly those employing 1,2,3- and 1,2,4-triazines, 5 are a valuable synthetic complement to traditional and more contemporary 6 condensation methods. 7 In comparison, merged cycloaddition/cycloreversion approaches for the direct synthesis of 2-pyridones are not common; 8 however, Hoornaert and co-workers validated the possibility of this approach using cycloaddition of chlorinated pyrazinone intermediates.…”
mentioning
confidence: 99%
“…The absolute configuration of naphthalene (+)-7 d was determined to be (S) by the anomalous dispersion method (Figure 1). [18] This transformation represents another synthetic utility of the present cascade reaction product. The desired alcohol (+)-7 a was indeed obtained with almost the same level of chirality transfer as that obtained with the cationic rhodium(I)/(R)-xylbinap complex (68 % ee, Scheme 4).…”
Section: Methodsmentioning
confidence: 86%
“…With cycloalkanone-derived substrates 1 i and 1 j, the carbonyl ene reaction did not even succeed at 80 8C. [18,19] In order to confirm whether the cationic rhodium(I) complex catalyzes the carbonyl ene reaction step, the isolated aldehyde (+)-5 a (78 % ee), prepared from 1 a by using the cationic rhodium(I)/(R)-xyl-binap catalyst, was treated with the cationic rhodium(I)/rac-binap complex (10 mol %) at 80 8C. The absolute configuration of naphthalene (+)-7 d was determined to be (S) by the anomalous dispersion method (Figure 1).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…[1] Danheiser and co-workerss howed that intermolecular cascade reactions could efficiently yield bicycles and tricycles (depending on the nature of the dienophile). [11] The diyne species (3)u ndergoes an intramolecular propargylic ene reactiont o form an intermediate allene followed by the concomitantintermolecular Diels-Alder reaction in the presence of ad ienophile to yield the polycyclic product (Scheme 2). Parsons and coworkers have also demonstrated that an intra/intermolecular reactioncan take place.…”
mentioning
confidence: 99%